Coherent potential vorticity maxima and their relationship to extreme summer rainfall and tropical cyclone genesis - Hoang, Lam Phuc (Monash University. Faculty of Science. School of Earth, Atmosphere and Environment, 2016)
Extreme rainfall and tropical cyclones (TCs) are of great interest to the meteorological community. Their influences extend to many different industries such as agriculture, airlines and insurance, and they keep challenging forecasters in making their decisions. A great deal of effort has been put into improving our understanding of the extreme rainfall and tropical cyclone genesis, as well as increasing the forecast accuracy in the numerical weather prediction models and operational forecast systems. The research presented here examines extreme rain events and tropical cyclone genesis from a potettial vorticity (PV) viewpoint using mainly European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim (ERAI) reanalysis. PV is used as a diagnostic of the atmospheric flow in this research and the main meteorological field to investigate the synoptic conditions during extreme rain events and the formation of tropical cyclones. The objective tracking technique introduced by Berry et al. (2012) is used to track cyclonic PV centres on three isentropic surfaces (315 K, 330 K, and 350 K) and construct a global climatology of the coherent cyclonic PV centres density and motion. It is found that the coherent cyclonic PV centres lie predominantly on the equatorward flank and commonly travel around the periphery of the mean subtropical anticyclones. This motion implies the transport of cyclonic PV centres from the midlatitudes to the tropics on the eastern side of the anticyclones. One area in which the meridional transport of the PV from the extratropics toward the tropics is large is the east coast of Australia during December-January-February (DJF). Extreme rainfall is defined by the 95th percentile of the daily rainfall time series for particular season from 1997 to 2009 from Global Precipitation Climate Project (GPCP). It is shown that 95% and 82% of the extreme rain days in the Australian and north African tropics, respectively, are associated with a cyclonic PV centre. The composites based on extreme rain days in the two regions also show a coherent cyclonic PV centre upstream of the precipitating region. The vertical structures are broadly the same, although the amplitude is a little larger in the Australian tropics. The vertical wind structures reveal that the synoptic pattern in the Australian tropics is similar to a mesoscale convective system (MCS), whereas in the north African tropics it is closer to an easterly wave. It is also shown that after extreme rain events in the Australian tropics, the large-scale circulation dramatically changes with the positive rainfall anomaly regions and the monsoon trough moving far southward, and with rainfall over west Australia and monsoon trough frequency in the extratropics increasing significantly. Tropical cyclones are usually associated with coherent cyclonic PV centres in the lower and mid-troposphere. It is found that there are approximately 3 - 4 TCs per year in North Atlantic which have associated coherent cyclonic PV centres originating in the extratropics (i.e. poleward of 23.5◦), whereas in South Pacific, approximately 10 TCs are found over 30 years (1980 - 2009) with associated coherent cyclonic PV centres originating in the extratropics. Tropical cyclone Larry (March 2006) formed in the Coral Sea and was associated with a 330 K isentropic coherent cyclonic PV centre originating in the extratropics is investigated here. PV filamentation along the east coast of Australia plays a role in the generation of TC Larry, and Larry is the only TC in March-April-May season that has an associated coherent PV maximum detected first in the extratropics. It is also found that Rossby waves breaking (RWB) characterised by an elongated upper-level PV trough over the Coral Sea intensifies a tropical disturbance into a tropical depression before a second RWB event associated with a cold surge, combines with small vertical wind shear, to intensify the low-level vorticity eventually forming TC Larry.